2021
DOI: 10.21248/jfml.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Some systematic aspects of self-initiated mobile device use in face-to-face encounters

Abstract: This contribution is interested in the interactional management of mobile phone use in face-to-face encounters. Early observational studies of mobile phone use have emphasized the tension between the participants’ presence in “public” spaces and their “private” activities on mobile phones. This assumed dichotomy and possible conflict between different communication involvements will be revisited by using a conversation analytic approach to mobile phone use in video recorded everyday encounters among friends an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus far, little conversation analytic research of such practices has been reported . Reeves and Brown (2016) and Oloff (2019) examined how social media use is embedded in everyday face-to-face activities, and Reeves et al (2017), in their work on game studies, considered how interaction inside a game can be combined with the study of players' interaction with each other and with spectators in the face-to-face context.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, little conversation analytic research of such practices has been reported . Reeves and Brown (2016) and Oloff (2019) examined how social media use is embedded in everyday face-to-face activities, and Reeves et al (2017), in their work on game studies, considered how interaction inside a game can be combined with the study of players' interaction with each other and with spectators in the face-to-face context.…”
Section: Introductionmentioning
confidence: 99%